Ketidaksetaraan Gender dalam Kajian Tasawuf - Desty Rahmawati; A. Halil Thahir; Robingatun Robingatun; Ach. Shodiqil Hafil (Gunung Djati Conference Series, 2023)
The purpose of this research is to discuss gender inequality in the study of Sufism. This study uses a qualitative approach with the method of library research (library research) by collecting relevant literature and then analyzing it according to the problems discussed. The results and discussion of this study is that there is gender inequality in the study of Sufism which is characterized by a lack of attention to female Sufis. This invites the public's perception that a Sufi is a man. The lack of attention to female Sufis is due to society's lack of trust in the spiritual level of female Sufis and also the limited space for women to move in the social order.